2015
DOI: 10.1007/s00401-015-1404-5
|View full text |Cite
|
Sign up to set email alerts
|

M. leprae components induce nerve damage by complement activation: identification of lipoarabinomannan as the dominant complement activator

Abstract: Peripheral nerve damage is the hallmark of leprosy pathology but its etiology is unclear. We previously identified the membrane attack complex (MAC) of the complement system as a key determinant of post-traumatic nerve damage and demonstrated that its inhibition is neuroprotective. Here, we determined the contribution of the MAC to nerve damage caused by Mycobacterium leprae and its components in mouse. Furthermore, we studied the association between MAC and the key M. leprae component lipoarabinomannan (LAM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 18 publications
4
29
0
5
Order By: Relevance
“…We also found that LAM deposition was also significantly higher in skin lesions of ENL and RR patients compared to BL patients with no reaction. We previously showed that there is a correlation between the BI or LAM and MAC deposition in nerves of leprosy patients [17]. Here, we show that both the BI and LAM also correlate with C3d and MAC deposition in skin of leprosy patients indicating a strong link between the presence of M .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We also found that LAM deposition was also significantly higher in skin lesions of ENL and RR patients compared to BL patients with no reaction. We previously showed that there is a correlation between the BI or LAM and MAC deposition in nerves of leprosy patients [17]. Here, we show that both the BI and LAM also correlate with C3d and MAC deposition in skin of leprosy patients indicating a strong link between the presence of M .…”
Section: Discussionsupporting
confidence: 70%
“…leprae induced nerve damage [17]. MAC was also found deposited on axons in nerve biopsies of leprosy patients.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly in the context of leprosy, we showed recently that the membrane attack complex (MAC) of complement is generated upon cognate interaction of the axon of the peripheral nerve with the M. lepraespecific PAMP LAM [19]. In addition, we showed that MAC formation results in nerve damage, and its inhibition is neuroprotective in a mouse model for M. leprae-induced nerve damage.…”
Section: Discussionmentioning
confidence: 93%
“…Deposits of MAC or the soluble terminal complement complex (TCC) were demonstrated in association with damaged nerve in leprosy patients [19]. In this context, we recently showed the association between persistence of the M. leprae antigen LAM and complement activation in the damaged nerve.…”
Section: Introductionmentioning
confidence: 95%
“…The LAM of M. tuberculosis is a major modulator in the immune response to tuberculosis [98]. However, little of the corresponding research has been conducted in the case of leprosy, and only two studies are reported in the literature [99,100].…”
Section: Modulation Of Innate Immunitymentioning
confidence: 99%